IMPLEMENTASI KEBIJAKAN PENANGANAN KONFLIK ANTAR PERGURUAN SILAT DI KABUPATEN MADIUN - Asiyah, Siti Nur; Suwardi, Suwardi; Suryo Sardjono, Herning (Master of Public Administration, Universitas Slamet Riyadi, 2024)
The research in this thesis is motivated by conflicts between Perguruan Silat which often occur in the Madiun Regency area. To date, the Madiun Regency Government continues to strive to prevent conflict between organizations by implementing Conflict Prevention Efforts as stated in Government Regulation Number 2 of 2015 concerning the Implementation of Law Number 7 of 2012 concerning Handling Social Conflict. The research objective in writing this thesis is: To create a scientific description of the implementation of conflict management policies between Perguruan Silat in Madiun Regency. This type of research is qualitative with a descriptive approach. Data Collection Techniques using Literature Study and Field Study (Interviews and Documentation). Data analysis was carried out by data reduction, data presentation and drawing conclusions. To test the validity of the data, extended observations, increased persistence, source triangulation, techniques and time were used. From the results of this research, the author concludes that: (1) The Madiun Regency Government, in this case implemented by the Madiun Regency National Unity and Politics Agency, has implemented conflict management in the form of activities: (a) Workshops and Development of IPSI Members, (b) Formation of an Integrated Team Handling Social Conflict, (c) Establishing a Madiun Regency Regional Early Warning Team, (d) Establishing a Community Early Alert Forum, (e) Implementing the Waskita Purabaya Early Warning System, (f) TNI/Polri Synergy in Securing Community Activities. (2) In implementing the Conflict Management Policy, support from stakeholders and budget support are supporting factors in implementing the implementation of this policy. (3) The shortage of employees at Bakesbangpol Madiun Regency is an obstacle to implementing conflict management policies.